A inserção internacional cubana a partir das relações com o Caribe (1959-2016) - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This work has the objective of analyzing relations between Cuba and the Caribbean countries, through the integration processes and bilateral agreements. These relations are characterized by South-South cooperation, besides the soft power exercised by Cuba through social diplomacy in the Caribbean countries, by the export of issues related to health, sports, education, among others. These relations intensify with the end of the Soviet Union and the Cold War, thus causing the loss of Cuba's main economic, commercial and military partner, resulting in an internal and external crisis. Thus, from the beginning of the 1990s, it began to intensify its relations with other countries of the international system, with the Caribbean countries being one of the first options for such relations due to the geographical, historical and cultural proximity between them, besides the fact Cuba is characterized by one of the main countries in the region. These relations are characterized by the creation of integration processes, such as the Caribbean Community (CARICOM) and the Association of Caribbean States (ACS) in 1995, where Cuba participates as a founding state, thus playing a significant role in the development of these integrationist blocs. In the 21st century, there have been other integration groups between Cuba and the Caribbean countries, where the Bolivarian Alliance for Our America-Trade Treaties for Peoples (ALBA-TCP) and the Community of Latin American and Caribbean States (CELAC) are extremely important in Cuban relations with the international system. Thus, through these relations the Caribbean region directly influences the international insertion and the Cuban maintenance in the international system.
The Cuban international insertion from relations with the Caribbean (1959-2016)
Keywords: Cuba; Caribe; Cooperação Sul-Sul; Relações Internacionais; South-South Co-operation; International relations; CNPQ::CIENCIAS SOCIAIS APLICADAS